On the Narrative of Ernest Koliqi - The Role of Detail in Psychological Catharsis - Alimerko, Irena; Alisa Velaj, (European Journal of Multidisciplinary Studies, 2018)
It is the detail that enables the crossing from one time to another one, from one state to another inside the narrative of Ernest Koliqi. Let's look more concretely, through the analysis of the stories, how this detail doesn’t only make shifts of times and states, but overcoming is exactly the "boiling point" of each story, the station where are overthrown all illusion or "real meaningfulness”, which can be created into the reader before the sudden arrival of this detail. The permutations of situations do not necessarily result in shifts of time, while the changes of the time necessarily contain changes into the situations. To look at these metamorphoses, we are lighting on the stories "Did I leave it to you?", "Welter", "Moon of blood", "Little personage" and "It was found behind the bush". The story entitled “Welter “has on the focus a sharp social situation, which inevitably leads to the degeneration of the moral character of the mother and daughter, Sila and Lina. The story entitled "Little personage" chooses as the name of the protagonist that state which has invaded his soul and mind; a real drama in front of the inability to be free, far from the handcuffs of a deeply material world, with the walled borders that do not let his dreamlike soul to breath. Another story, in which the detail immerses the protagonist in a reflective state, is also "Moon of blood". The detail of the Moon turns into a controversy over the development of the subject. At first glance, attractiveness to the moonshine simply encourages the passage or the return from time to time (bearing within the lattermost also the changes in the characters' situations) and seems to "wax the guy" the image of this detail actually appears "to wax" completely the girl. Keywords: detail, psychological catharsis, psychological cogitations, the past and the present
Keywords: detail, psychological catharsis, psychological cogitations, the past and the present